Pharmacy Practice and Administration - Adunlin, Georges (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
The scope of the Special Issue is research and reviews on evaluations of current practice, innovations in medication management, developments in therapeutics, and pharmaceutical science research that informs and improves practice and administration, as well as the social and administrative pharmacy. We will mainly feature original research, reviews, short reports, and clinical studies, but also case reports, descriptive/how-to, and commentary submissions for consideration.